2020
DOI: 10.1108/tr-07-2020-0344
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the consequences of COVID-19 on tourist behaviors: perceived travel risk, animosity and intentions to travel

Abstract: Purpose This paper aims to report on the findings emerging from an international study focused on the COVID-19 pandemic impact on travel attitudes and behavioral intentions . Design/methodology/approach An online survey created with SurveyMonkey was distributed to a sample of 216 international travelers who were at least 18 years of age. Findings The findings suggest that attribution theory (locus of control) may account for international travel. Individuals attributing the spread of COVID-19 to their own … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 74 publications
4
69
0
3
Order By: Relevance
“…In studies related to COVID-19, some research has demonstrated the influence of risk perceptions of COVID-19 on tourism (Zhu and Deng, 2020; Qiu et al , 2020). Some also found that there are significant differences between various generational cohorts concerning perceived travel risk during COVID-19 (Abraham et al , 2020). In this article, we used social cognitive theory to make risk perception one part of personal processes and obtained similar results indicating that risk perceptions of COVID-19 reduce people’s willingness to travel in personal processes.…”
Section: Resultsmentioning
confidence: 99%
“…In studies related to COVID-19, some research has demonstrated the influence of risk perceptions of COVID-19 on tourism (Zhu and Deng, 2020; Qiu et al , 2020). Some also found that there are significant differences between various generational cohorts concerning perceived travel risk during COVID-19 (Abraham et al , 2020). In this article, we used social cognitive theory to make risk perception one part of personal processes and obtained similar results indicating that risk perceptions of COVID-19 reduce people’s willingness to travel in personal processes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the sensational media coverage of crisis events heightens tourists’ fear (Pforr and Hosie, 2008). Specifically, infectious diseases such as COVID-19 have been verified to affect travel behaviour and destination choice (Abraham et al , 2020), and complaints will proliferate if tourists’ demands are not met. The external shocks caused by the crisis have led to the most severe breakdown in the tourism service system.…”
Section: Introductionmentioning
confidence: 99%
“…As we write, COVID-19 is still very much with us so the analysis provided here draws on a range of scientist journals (Baum and Hai, 2020) and secondary sources, which can be formally verified at this time. The literature relation to the COVID-19 pandemic is being extended and this is focused on aviation and tourism sectors (Abraham et al , 2020; Albers and Rundshagen, 2020; Bock et al , 2020; Budd et al , 2021; Chinazzi et al , 2020; Henríquez et al , 2020; Maneenop and Kotcharin, 2020; Melly and Hanrahan, 2020; Mustapha et al , 2020; Nakamura and Managi, 2020; Serrano and Kazda, 2020; Sharun et al , 2020; Suzumura et al , 2020; Uğur et al , 2020; Wen et al , 2020; Wenzel et al , 2020; Winston, 2020; Ye et al , 2020, etc.). The literature shows the link between airports and airlines to attract passengers to the tourist destination.…”
Section: Methodsmentioning
confidence: 99%
“…An extraordinary crisis such as the COVID-19 pandemic means that there is little time for response organization and planning (Wenzel et al , 2020). Following Abraham et al (2020), the COVID-19 disease has taken an unprecedented toll on travel and tourism, lives and livelihoods. Pandemic can be expected to have far-reaching impacts on tourists’ consumption behavior (Wen et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%